Individualised therapy is more cost-effective than dose intensification in patients with Crohn's disease who lose response to anti-TNF treatment: a randomised, controlled trial. Issue 6 (22nd July 2013) - Steenholdt, Casper; Brynskov, Jørn; Thomsen, Ole Østergaard; Munck, Lars Kristian; Fallingborg, Jan; Christensen, Lisbet Ambrosius; Pedersen, Gitte; Kjeldsen, Jens; Jacobsen, Bent Ascanius; Oxholm, Anne Sophie; Kjellberg, Jakob; Bendtzen, Klaus; et al.
Abstract : Objective: Although the reasons for secondary loss of response to infliximab (IFX) maintenance therapy in Crohn's disease vary, dose intensification is usually recommended. This study investigated the cost-effectiveness of interventions defined by an algorithm designed to identify specific reasons for therapeutic failure. Design: Randomised, controlled, single-blind, multicentre study. 69 patients with secondary IFX failure were randomised to IFX dose intensification (5 mg/kg every 4 weeks) (n=36) or interventions based on serum IFX and IFX antibody levels using the proposed algorithm (n=33). Predefined co-primary end points at week 12 were proportion of patients responding (Crohn's Disease Activity Index (CDAI) decrease ≥70, or ≥50% reduction in active fistulas) and accumulated costs related to treatment of Crohn's disease, expressed as mean cost per patient, based on the Danish National Patient Registry for all hospitalisation and outpatient costs in the Danish healthcare sector. Results: Costs for intention-to-treat patients were substantially lower (34%) for those treated in accordance with the algorithm than by IFX dose intensification: €6038 vs €9178, p<0.001. However, disease control, as judged by response rates, was similar: 58% and 53%, respectively, p=0.81; difference 5% (−19% to 28%). For per-protocol patients, treatment costs were even lower (56%) in the algorithm-treated group (€4062 vs €9178, p<0.001) and with similar response rates (47% vs 53%, p=0.78; difference −5% (−33% to 22%)). Conclusions: Treatment of secondary IFX failure using an algorithm based on combined IFX and IFX antibody measurements significantly reduces average treatment costs per patient compared with routine IFX dose escalation and without any apparent negative effect on clinical efficacy. Trial Registration No: NCT00851565.